Money and Inflation in Al-Maqrizi's Islamic Economic Theory - Sumper Mulia Harahap (Institut Agama Islam Negeri Padngsidimpuan, 2023)
Money related thoughts and inflation are things that Muslim scholars rarely observe. Al-Maqrizi proposed numerous ideas on money and inflation, and the goal of this research is to discover Al-Maqrizi's theory of money and inflation, as well as ways to cope with inflation. A qualitative research method using a conceptual approach or character study was applied. Content analysis was performed to analyze the data. The study's findings indicate that currency based solely on gold and silver can be accepted as a standard of worth. According to Al-Maqrizi, there are two types of inflation: natural inflation and inflation caused by human error (corruption and bad management, high taxation, and a rise in money circulation).